Benign Phyllodes Tumour of the Breast. Literature Review and Case Presentation - Lidia Torres Aja; Neylín Caballero Aja; José Alberto Puerto Lorenzo (Universidad de las Ciencias Médicas de Cienfuegos, 2017)
Phyllodes tumor is an uncommon fibroepithelial neoplasia, with an epithelial benign component and mesenchymal component that can be malignant or benign and represents only 0.3 to 0.4 % of all breast tumours. It appears mainly in the female sex; a few male cases have been reported worldwide and they are unusual in girls and adolescents. It appears during the fourth or fifth decade of life. A case of a 49 year old patient is presented who came to the mastology consultation complaining of a protuberance which occupied the two left breast external quadrants. It was diagnosed by paraffin-embedded biopsy as benign phyllodes tumor of the breast. Due to the infrequent presentation of this entity, the publication of this case is considered of scientific value.